Performance of Bus Services in Urban Area: A Case Study in Penang, Malaysia - Norhisham S.; Abu Bakar M.F.; Zamree S.F.; Azlan N.N.I.M.; Mohamad A.M.; Katman H.Y. (IOP Publishing Ltd, 2023)
Since the escalated industrialisation and urbanisation process began traffic congestion has been a serious problem in many Malaysian cities. One of the solutions for the traffic congestion is by promoting public transport. Public transport is needed to manage the transport in cities. In 2007, a corporate body owned by the Malaysian Government named Prasarana Malaysia, introduced the Rapid bus service in Penang. Currently, Rapid bus is the main public transport operator in Penang. However, the bus service had some setbacks and passengers had publicly voiced their dissatisfaction. Therefore, to encourage more people in using the public transport, a better public transport system should be provided and improved occasionally. Previous comprehensive studies were inadequate, and thus a detailed analysis of the bus service performance in Penang is needed. The Transit Capacity and Quality of Service Manual (TCQSM) was chosen for guidelines. Based on reviews from journals and papers three (3) objectives which focused on service frequency, on time performance and passenger load factor were chosen for the study. The study was conducted to evaluate the bus service performance in Penang. The study results obtained the quality of service (QOS) of D for the Rapid bus service performance in Penang, which was regarded as satisfactory. This showed that buses in Penang needed to be greatly improved to change the passengers perceptions. 2022 Institute of Physics Publishing. All rights reserved.